A History of the Islamic World, 600-1800 Empire, Dynastic Formations, and Heterogeneities in Pre-Modern Islamic West-Asia - Steenbergen, J. van (Routledge, 2021)
A History of the Islamic World, 600-1800 supplies a fresh and unique survey of the formation of the Islamic world and the key developments that characterize this broad region's history from late antiquity up to the beginning of the modern era. Containing two chronological parts and fourteen chapters, this impressive overview explains how different tides in Islamic history washed ashore diverse sets of leadership groups, multiple practices of power and authority, and transformed imperial and dynastic discourses in a theocratic age. A text that transcends many of today's popular stereotypes of the premodern Islamic past, the volume takes a holistically and theoretically informed approach for understanding, interpreting and teaching premodern Islamic history. Jo Van Steenbergen identifies the Asian connectedness of the socio-cultural landscapes between the Nile in the southwest to the Bosphorus in the northwest, and the Oxus (Amu Darya) and Jaxartes (Syr Darya) in the northeast to the Indus in the southeast. This abundantly illustrated book also offers maps and dynastic tables, enabling students to gain an informed understanding of this broad region of the world. This book is an essential text for undergraduate classes on Islamic History, Middle East Studies, and Religious History.